การพัฒนาสิ่งทดแทนอาหารเพาะเชื้อที่มีนมเป็นองค์ประกอบและการหาภาวะที่เหมาะสมสำหรับการผลิต Bifidobacterium animalis - ปัณณธร ทวีเทพไทกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This study was carried out for development of substitute for milk based medium for production of B. animalis TISTR 1925. An initial screening using a 23 full factorial design was used to identify the impact on cultures of the various components of the medium which were molasses, yeast extract and urea. Statistical analysis suggested that yeast extract and interaction of molasses and yeast extract had a significant positive effect on growth whereas urea variable and another interaction terms had negative effect. The regression equation indicates that increasing of yeast extract concentration would increase of bacterial growth, whereas increasing of molasses concentration would decrease of bacterial growth. Therefore, steepest ascent is used to investigate the ration of molasses and yeast extract. The results indicated that the highest viable cell count was obtained at molasses and yeast extract concentration 46.4 g/L and 10 g/L, respectively. The medium optimization by using a central composite circumscribed (CCC) design, indicated the optimum points of 46.5 g/L molasses and 8 g/L yeast extract. The repeated experiments were performed to verify the predicted optimum, viable cell count of 9.2495 log10 cfu/mL. The calculated cost of the raw materials used in the substituted medium developed could reduce cost effectively by 20.36 % and 69.51 % comparing to the milk based medium and MRS broth, respectively. The condition to improve the cultivation in a substituted medium developed the growth performance in a 15 L fermenter. The growth performance was improved when the culture condition at agitation speed 200 rpm and pH 6.0, specific growth rate of 0.9835 h-1 and maximum viable cell count of 9.3116 log10 cfu/mL.